Nilai Rerata Volume Trombosit, Rasio Trombosit Limfosit, Rasio Rerata Volume Trombosit-Limfosit sebagai Prediktor Tingkat Keparahan Sindrom Koroner Kronik - Wijaya, Friska; Limantoro, Charles; Fitria, Indah; Suharti, Catharina; Nugroho, Trilaksana (RSUP Dr. Kariadi, 2023)
BACKGROUND: The increase in platelet aggregation and inflammation play an essential role in atherosclerosis. Furthermore, the level of activity depends on their size, with larger platelets facilitating the thrombosis process. Severe Coronary Artery Disease (CAD) is associated with low lymphocyte count. It is also linked with Mean platelet volume [MPV], Platelet Lymphocyte Ratio [PLR], and Mean Platelet Volume to Lymphocyte Ratio [MPVLR]. OBJECTIVE: This study aims to investigate MPV, PLR, and MPVLR as predictors of the severity of Coronary Artery Lesion in Chronic Coronary Syndrome (CCS) using the Gensini score. METHOD: This is a cross sectional study conducted in Dr. Kariadi General Hospital, involving a total sample of 68 respondents. Furthermore, CCS were evaluated before conducting coronary angiography. The study comprises of two group of patients divided according to their Gensini scores, namely mild and severe, for ≤ 20 and > 20, respectively. MPV, PLR, and MPVLR were then compared between the two groups. RESULT: At a cut-off level of 3.4, MPVLR predicted the coronary artery severity with a sensitivity, specificity, positive predictive value (PPV), and negative predictive value of 80%, 50%, 82%, and 47% (area under the curve [AUC] 0.67; 95% confidence interval [CI], 0.52-0.82; p 0.029). Meanwhile, its value ≥3.4 has OR 1.55; 95% CI, 0.99-2.43; p 0.034. CONCLUSION: This study conclude that MPVLR ≥3.4 can be used as a predictor of Coronary Artery Lesion Severity based on the Gensini score in CCS cases.